Hash functions : analysis study - AbdulMajeed, Khanssaa Munthir (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2013)
While the some weaknesses have appeared in many hash functions such as MD4, MD5, RIPEMD-family and the series of Secure Hash Algorithm (SHA) families such as, SHA-0, SHA-1, SHA-2, with a number of SHA-3. Thus, National Institute of Standard and Technology (NIST) has suggested different principles to avoid the blunders, and to choice the ideal quality of hash function, that to be a measurement in future of hash function generations. Therefore, the goal of the NIST contenders in SHA-3 between the hash functions is to be chosen as the winner in the end of 2012, or the beginning of 2013. Therefore, for this reason the research addresses the comparative study of the finalist SHA-3 candidates in: design and structure, complexity, with performance and cost, to measure the robustness of the algorithms through the Fundamentals Security Measurement Factors of Hash Function (FSMFHF) of Secure Hash Algorithm (SHA). As a result, from this comprehensive comparison study between the finalist SHA-3 candidates such as; BLAKE, Grostl, JH, Keccak, and Skein, a choice can be made as to the ideal security algorithm against different attacks in suitable structure design of high utilizing of message distribution with high trade-off of speed/ area performance in low cost. Therefore main idea in this research is classify, comparison, and analysis for all five SHA-3 candidates of finalist, and studying the details of these five candidates that in Round 3 by using different structures and different design approaches, and identifying whether the complexity for each design. Thus, this research found a JH hash function is the faster in implementation followed by Grostl hash function, after that Keccak hash function, which gets best security of the hash function applications for different industry structures, as well as supporting a security of different size of data in computer science.